Perceived barriers to physical activity and their predictors among adults in the Central Region in Saudi Arabia: Gender differences and cultural aspects - Osama Abdelhay; Mohammad Altamimi; Qusai Abdelhay; Marwan Manajrah; Ayla M. Tourkmani; Mutaz Altamimi; Taghreed Altamimi (PLoS ONE, 2025)
Objective To assess the perceived barriers hindering physical activity among adult residents of Riyadh, Saudi Arabia, and to identify associated sociodemographic and health-related factors, focusing on gender differences and cultural aspects. Methods A cross-sectional survey was conducted from the 9th of January 2022 to the 2nd of February 2023, involving 7,903 physically inactive participants aged 18 to 80. Participants were recruited using a two-stage cluster sampling method from the Central Region of Saudi Arabia. In the first stage, subregions based on the administrative distribution by the Medical Service Department were selected. In the second stage, private and public entities within these subregions were identified from governmental agency lists. Participants were then conveniently approached within these entities. Data were collected using a validated questionnaire, the Perceived Barriers to Being Active Questionnaire (PBAQ), assessing sociodemographic characteristics, health history, dietary habits, and perceived internal and external barriers to physical activity. Results Of the participants, 67.2% were male, with a mean age of 36.45 ± 13.69 years. Approximately one-third (35%) reported experiencing at least one internal barrier to physical activity, while 64.3% reported 1–2 internal barriers. For external barriers, 76.5% faced 1–2 barriers. The most common internal barriers were laziness (40.2%) and lack of self-motivation (27.5%); the most prevalent external barriers were lack of facilities (20.2%) and long working hours (19.6%). Females were significantly more likely than males to report cultural reasons (odds ratio [OR] = 4.83; 95% confidence interval [CI]: 4.06–5.76; p < 0.001) and religious reasons (OR = 3.31; 95% CI: 2.59–4.23; p < 0.001) as internal barriers. Multivariate analysis revealed that females were 14% more likely than males to report external barriers to physical activity (OR = 1.14; 95% CI: 1.04–1.25; p = 0.018), suggesting gender plays a role in perceived external obstacles. Additionally, older age, higher body mass index, higher education level, marriage, certain employment statuses, and chronic diseases were significantly associated with increased reported internal and external barriers. These findings highlight the complex interplay of demographic and health-related factors influencing physical activity participation. Conclusions There is a high prevalence of both internal and external barriers to physical activity among Saudi adults, with notable gender differences influenced by cultural factors. Females were more likely to report cultural and religious reasons as barriers. Tailored policies and interventions are urgently needed to address these barriers, such as promoting gender-specific physical activity programs, integrating physical activity into workplaces, enhancing public facilities, and conducting culturally sensitive educational campaigns. Addressing both internal motivations and external obstacles is essential to increase physical activity levels and combat the rising burden of non-communicable diseases in Saudi Arabia.